Self-assessment in anatomy and physiology in health and illness : Ross & Wilson - Waugh, Anne, ....-; Grant, Allison, ....- ([s.l.] : Elsevier, 2019)
This handy self-assessment paperback contains over 500 multiple-choice-questions to help readers evaluate their understanding of introductory level human biology. Fully indexed, with helpful explanations given throughout the answer section, the book will be ideal for students of nursing and allied health professions, biomedical and paramedical science, operating department practice, and complementary therapy and massage therapy. Over 500 MCQs support revision and learning Ideal for individual use or in an informal group setting Perfect prior to exams and/or for use during ‘placement breaks' or ‘on the move'!